Rethinking Open Society - Roch, Stefan; Ignatieff, Michael (Book collections on Project MUSE., 2018)
The Rethinking Open Society project is about the heart and the soul of CEU's mission. It brings leading thinkers to CEU to examine open society, its history, its achievements and failures and its future prospects in a world where its ideals are under threat. Between January and May 2017, CEU was privileged to host 12 distinguished academics, covering a wide range of issues, cutting to the core of what Open Society means in our day and age.